rpl-11.1 Knockdown Disturbs Translation Machinery and Proteostasis in Caenorhabditis Elegans (Global Journal of Science Frontier Research, 2024)
An array of human chronic diseases such as Alzheimer s disease Huntington s disease and Parkinson s disease are related to defects in cellular proteostasis and the formation of protein aggregates Using Caenorhabditis elegans PP563 a model organism developed for studying proteostasis stress we can elucidate the biological role of specific genes and proteins involved in translation and proteostasis advancing our understanding of relevant pathologies and therapeutics Here we report the knockdown of rpl-11 1 in C elegans leads to disturbance in protein translation and proteostasis pathways including the Ubiquitin-Proteosome System UPS and selective autophagy We confirmed the importance of rpl-11 1 in ensuring correct ribosome biogenesis and translation accuracy We also demonstrated that both the UPS and selective autophagy are involved in the clearance of misfolded and aggregated proteins A minor experiment in this study revealed the importance of rpl-11 1 in germline proliferation
Keywords: rpl-111; caenorhabditis elegans; RNAi; ubiquitin-proteosome system; selective autophagy; germline apoptosis